Impact of the bitewing radiography exam inclusion on the prevalence of dental caries in 12-year-old students in the city of Franca, São Paulo, Brazil Impacto da inclusão do exame radiográfico interproximal na prevalência de cárie dentária de escolares aos 12 anos no município de Franca, São Paulo, Brasil - Soraya Fernandes Mestriner; Luiz Carlos Pardini; Wilson Júnior Mestriner (University of São Paulo, 2006)
INTRODUCTION: The pattern of development of carious lesions has changed. The carious lesion has been progressive and reaches the dentin without showing alterations in the clinical aspects. OBJECTIVES: To determine the prevalence of caries in 12-year-old students in the city of Franca - São Paulo, Brazil, during the year of 2003, and to evaluate the additional value of bitewing radiograph to detect hidden carious lesions in permanent molar dentin. MATERIALS AND METHODS: A probabilistic sample composed of two hundred and fifty six (256) students, from public and private schools, was submitted to a cross-sectional study through examination by a calibrated examiner, in order to detect the caries prevalence, using the methodology recommended by the World Health Organization (WHO). For 66% of the sample, bitewing radiographs of the permanent molar region were obtained. The images were analyzed by a calibrated examiner, who established the presence of hidden caries in teeth with radiolucency in dentin, yet considered healthy in the epidemiological survey. RESULTS: The prevalence of dental caries in epidemiological exam without (WHO) and with (WHO/R) the inclusion of hidden caries lesion was 54% and 64%, and the DMFT index was 1.73 and 1.92 respectively. CONCLUSION: Utilization of the method of bitewing radiographic diagnosis significantly increased (p<0.001) the prevalence of caries in the studied population. INTRODUÇÃO: Ocorreram mudanças no padrão de desenvolvimento da lesão de cárie. As lesões tem progredido e atingido a dentina, sem demonstrar alterações nos aspectos clínicos. OBJETIVOS: Determinar a prevalência de cárie em escolares de 12 anos no município de Franca - SP, Brasil, no ano de 2003 e avaliar o valor adicional da radiografia interproximal para detecção de lesões de cárie em dentina de molares permanentes na prevalência de cárie. MATERIAIS E MÉTODOS: Desenvolveu-se um estudo transversal com uma amostra probabilística; em que foram realizados exames epidemiológicos por um examinador calibrado, em 256 escolares das redes de ensino público e particular, utilizando a metodologia recomendada pela OMS; e em 66% da amostra, foram obtidas radiografias interproximais da região de molares permanentes. As imagens foram analisadas por um examinador calibrado; considerando dente com lesão de cárie oculta, aquele que apresentava radiolucidez em dentina no exame radiográfico e no entanto, estava hígido no levantamento epidemiológico. RESULTADOS: A prevalência de cárie dentária no exame epidemiológico sem (OMS) e com (OMS/R) a inclusão da lesão de cárie oculta foi de 54% e 64%, e os índices CPOD, 1,73 e 1,92 respectivamente. CONCLUSÃO: O emprego do método de diagnostico radiográfico interproximal aumentou significativamente (p<0,001) a prevalência da cárie na população estudada.